PEMBINAAN ANAK SEKOLAH MINGGU MELALUI MEDIA DIGITAL - Pattinama, Yenny Anita; Mondolu, Debby Christ; Sitindaon, Riky Handoko; Pasaribu, Ferdinan; Antang, Silvia Magdalena (STT Ebenhaezer Tanjung Enim, 2022)
Using the internet as a means of fostering and educating children is a good step during the current Covid-19 pandemic. Through Eben Kids Ministry shows, staff and students are required to be more creative and innovative in presenting shows so that each show can attract children's attention. Eben Kids Ministry is also designed in such a way that every child who watches the show is not only educated in spiritual matters but also trained to build creativity and ability in various things. The Southern Sumatra Regional Council and the Ebenhaezer Theological College are trying to build community service programs, and the institution gets support from parents and all Christians, especially those in the Tanjong Enim area and its surroundings.